Uji Daya Hambat Lendir Bekicot (Achatina Fulica) terhadap Pertumbuhan Bakteri Staphylococcus Aureus dan Salmonella Typhi - Kasih Purwati; Sukma Sahreni; Dhea Fajria Khasanah (Universitas Batam, 2022)
Background: Snail mucus (Achatina fulica) contains achasin protein which can inhibit the growth of Staphylococcus aureus and Salmonella typhi bacteria. This study aims to determine the effect of snail mucus (Achatina fulica) on the growth of Staphylococcus aureus and Salmonella typhi bacteria. Methods:This research is an experimental research using Posttest Only Control Group Design as the research design. This research was conducted at the Microbiology Laboratory, Riau University, from December 16, 2021 to January 11, 2022. The population of this study was pure culture of Staphylococcus aureus and Salmonella typhi. The sample consisted of 30 snails which had previously been adapted for 1 month. The negative control group was only given distilled water, the positive control group was given amoxicillin, treatment group 1 was given snail slime with a concentration of 30%, treatment group 2 was given snail slime with a concentration of 60%, and treatment group 3 was given snail mucus with a concentration of 90%. The result of this research will be analyzed using statistical test, ANOVA. Results:There is an inhibition of snail mucus (Achatina fulica) against the growth of Staphylococcus aureus and Salmonella typhi bacteria. The most effective results in inhibiting the growth of Staphylococcus aureus and Salmonella typhi bacteria is at a concentration of 90%. Conclusion:Based on the results of this study, it can be concluded that snail mucus (Achatina fulica) can significantly inhibit the growth of Staphylococcus aureus and Salmonella typhi bacteria.